Pengaruh Kepemilikan Asing, Komite Audit, dan Kinerja Keuangan terhadap Nilai Perusahaan - Lestari, Fita Dwi; Setiany, Erna (Politeknik Negeri Batam, 2023)
Corporate value is used by management in running the business to maximize shareholder wealth. Audit committees, foreign ownership, and financial performance have prospects in the future so that investors will be interested in investing. This population is a manufacturing company that pays out dividends during the period 2016 to 2021 which are listed on the Indonesia Stock Exchange. The sampling technique is 222 companies. The method used is panel data regression. The findings of foreign ownership, debt to equity, total asset turnover, net profit margin, and return on assets significantly affect company value, but audit committees, current ratios, and dividends have no significant effect on company value. It is suggested that the company can improve its financial performance to maximize profit, which reflects the company internally. In addition, foreign ownership can make decisions in the company's strategy to increase the value of the company.